PENGUJIAN USABILITAS USER EXPERIENCE PADA WEBSITE UBIQUITOUS BASED LEARNING (UBL) CLOUD PT POLARIS EDU PARTNERS MENGGUNAKAN METODE HEURISTIC EVALUATION MELALUI PENDEKATAN USABILITY NIELSEN MODEL - Hana Hanifah (2021)
The UBL Cloud website has 4331 users of student portal. The interface of the website currently does not meet user-friendly design standards, also PT Polaris Edu Partners has never evaluated its user interface to improve user experience. Thus, this research was conducted to test the usability and interface of UBL Cloud site from the user and expert preferences. The Usability testing of users is carried out by testing based on Nielsen Model indicators consisting of usability as a dependent variable and independent variables consisting of learning, efficiency, memory, errors, and user's satisfaction. The results of the analysis showed that the usability of the UBL Cloud website met users with an average value of 77.08%. Also between the independent variables (learning, efficiency, memory, error, and user satisfaction) have mutual influence simultaneously. Variables of efficiency, memory and user satisfaction have a partial effect on the usability variable, while the learning ability and error variables have no significant effect on the usability variable. Thus, in the test, the results of the hypotheses H2, H3, H4 were accepted while H1 and H3 were rejected. In the Heuristic Evaluation test by experts, there were 50 usability problems. Based on these problems, expert recommendations are also included which are used as references in making the re-design prototype of the UBL Cloud user interface website as a recommendation to PT Polaris Edu Partners for the development of the UBL Cloud website.